An open-source handheld extruder loaded with pore-forming bioink for in situ wound dressing. (September 2020) - Ying, G.; Manríquez, J.; Wu, D.; Zhang, J.; Jiang, N.; Maharjan, S.; Hernández Medina, D.H.; Zhang, Y.S.
Abstract: The increasing demand in rapid wound dressing and healing has promoted the development of intraoperative strategies, such as intraoperative bioprinting, which allows deposition of bioinks directly at the injury sites to conform to their specific shapes and structures. Although successes have been achieved to varying degrees, either the instrumentation remains complex and high-cost or the bioink is insufficient for desired cellular activities. Here, we report the development of a cost-effective, open-source handheld bioprinter featuring an ergonomic design, which was entirely portable powered by a battery pack. We further integrated an aqueous two-phase emulsion bioink based on gelatin methacryloyl with the handheld system, enabling convenient shape-controlled in situ bioprinting. The unique pore-forming property of the emulsion bioink facilitated liquid and oxygen transport as well as cellular proliferation and spreading, with an additional ability of good elasticity to withstand repeated mechanical compressions. These advantages of our pore-forming bioink-loaded handheld bioprinter are believed to pave a new avenue for effective wound dressing potentially in a personalized manner down the future. Graphical abstract: Image 1 Highlights: A low-cost portable handheld extrusion bioprinter was designed to achieve ergonomic operations. An aqueous two-phase emulsion bioink was optimized allowing pore formation. The pore-forming bioink was loaded in handheld extruder for in situ wound dressing. The transport of liquid and oxygen was improved in the porous hydrogel dressing. The spreading of encapsulated cells in the porous hydrogel dressing.